Simple shear behavior and constitutive modeling of 304 stainless steel over a wide range of strain rates and temperatures. (August 2021) - Jia, B.; Rusinek, A.; Pesci, R.; Bernier, R.; Bahi, S.; Bendarma, A.; Wood, P.
Highlights: Shear behavior of 304 stainless steel investigated over a wide range of strain rates from 0.001 to 39000 s −1 . Simple shear stress state with stress triaxiality and Lode angle parameter close to zero obtained. Strain rate sensitivity covering quasi-static (10 −3 –10 −1 s −1 ), dynamic (3000–6000 s −1 ) and very high (13000–39000 s −1 ) strain rate ranges analyzed. Due to the shear-tension stress state without hydrostatic pressure, no well-developed adiabatic shear bands were observed. Abstract: A novel single shear specimen (SSS) together with a correction coefficient method is used to study the deformation behavior of a 304 stainless steel under shear loadings. Shear stress-shear strain relations over a wide range of shear strain rates (0.001 to 39000 s −1 ) at three initial temperatures (77 to 473 K) are obtained experimentally. The effects of strain rate and temperature on the flow stress curves are determined. With increasing strain rate or temperature, the strain hardening rate decreases continuously. At the maximum strain rate of 39000 s −1, negative strain hardening rates are observed. At very high strain rates above 13000 s −1, a sharp increase in flow stress is observed, indicating a rapid rise in strain rate sensitivity. The fracture morphology of post-mortem specimens is analyzed and no well-developed adiabatic shear bands are observed. This may be due to the shear-tension stress state without hydrostatic pressure in the fracture process. Based on the experimentally obtained shear stress-shear strain curves, parameters of a modified Johnson-Cook (MJC) model are determined. A good agreement between experiments and model predictions is found, with an average error of 3.9%. Using finite element analysis, distributions of stress and strain components in the specimen shear zone is analyzed. It is found that the shear stress and shear strain play dominant roles, and a simple shear stress state with low stress triaxiality (0.015) and Lode angle parameter (0.014) is obtained. Graphical abstract: Image, graphical abstract